RANCANG BANGUN ALAT FIKSASI PEMERIKSAAN RADIOGRAFI ABDOMEN PROYEKSI LEFT LATERAL DECUBITUS - Dhea Mirza; Widya Nurmayanti; Devi Purnamasari (Perhimpunan Radiografer Indonesia (PARI), 2023)
ABSTRACT Background: Radiologic fixation device is a tool made of specially designed iron plate that is used by radiology officers to assist in treating patients. As in the LLD (Left Lateral Decubitus) projection abdominal radiography, non-cooperative patients need an assistive device to facilitate the examination. LLD projection abdominal fixation device This can be used to place cassettes of various sizes, limit patient movement, ensure that the cassette and grid remain attached to the posterior part of the patient without being touched by the patient's family, make the left side of the patient's abdomen not cut, and provide radiation safety to the patient, patient's family, and staff. This study aims to design a fixation tool for projection abdominal radiography examinations LLD and test tools. Methods: This research is an applied type of research by designing a fixation device for LLD. projection abdominal radiography examination as well as testing these tools through questionnaires and documentation studies. The research was conducted at the Radiology Laboratory of Awal Bros University from May to June. Results: The LLD projection abdominal examination fixation device, this tool composed of 5 components: patient seat, metal support, cassette holder, foam pad and strap. Conclusions: From the results of data collection using a questionnaire, it was found that the LLD projection abdominal examination fixation tool has met the performance test in accordance with the specifications of the tool and has good value in terms of the components of the tool, durability, efficiency of the tool and the resulting radiograph.